PENGEMBANGAN PROGRAM SOSIOMETRI SEBAGAI MEDIA PENGUNGKAPAN HUBUNGAN SOSIAL SISWA SMAN 9 MAKASSAR - Akhmad Harum (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2015)
This study aims to produce an application program sociometry connected to a computer which included a media component to analyze sociometry data and instruments at high school students, which can be directly used for a tutor by filling out an application and able to know the students' social relationships. The research used development model, with procedural which had been modified by the researcher. The subjects of this study is divided into subject experts, namely the subject of the instrument experts, IT and tutor as well as the subject of the trial, namely 6 students, 3 students in grades 2 and 3 others in grade 3, and overall supervising teachers at SMAN 9 Makassar. Withdrawal of study subjects using stratified random sampling technique. Data was collected through interviews, feasibility studies, questionnaire and documentation. Results of development research completed with two stages of the test, the experts test, as well as two stages of the revision, including revision based on expert testing and revisions based on testing small groups. Based on the feasibility study by expert test the general program, sociometry program as a disclosure of students’ social relations media gets 4.26% grading scale that is in the category feasible and based on a small group of test programs, sociometry at acceptance tests as much as 90% (very high) products declared acceptable and usable test as much as 90% (very high) products otherwise it can be used / implemented.